Development of Standard Instruments for Assessment of Performance Assessment of Android-Assed Regional Song for SMP - M Arvin Nugroho; Supriyadi Supriyadi; Wahyu Lestari (Budapest International Research and Critics University, 2022)
Development of a standard instrument for assessing performance in singing folk songs with the help of android is a development research with four problem formulations.The research method uses a research and development whose steps are adapted from the addie model. The results of the study resulted in a teacher's guide book and an android application containing standard instruments for assessing singing performance with the help of android, namely 1) the results of the needs analysis obtained by the standard instrument for assessing the performance of singing folk songs did not meet the requirements of validity, reliability, and practicality, 2) instrument validation was carried out by 4 validators, the instrument is worthy of testing with revisions, 3) reliability is analyzed using the analysis of intraclass correlation coefficients (correlation coefficients) intraclass . ) has a score of 0.826. Large-scale trials were carried out in two schools, namely SMP Negeri 9 Teluk Keramat with an 0.891 (SMPNegeri 5 Pontianak an average measure of 0.979 (very high). 4) instrument construct validation was analyzed using comparative analysis with one-way ANOVA it was obtained that the value of kmo > 0.5, i.e. 0.78 was declared valid. 5) The practicality of the instrument was analyzed by means of a questionnaire, it was obtained that the score interval had the lowest practicality value of 48 and the highest 80 of 20 teacher respondents and was declared practical. The conclusions of the development research carried out resulted in a teacher's guide book and an android application containing standard instruments for assessing performance in singing folk songs with the help of android. Teachers can use teacher manuals and applications in classroom learning when conducting learning evaluation activities.